Leadership style and job satisfaction among Malaysian Army College officer - Abdul Rahman, Mohd Ghazali; Abdullah, Mohd Yusuf; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2019)
Job satisfaction is regarded as a generally favorable or unfavorable attitude resulting from specific work areas, such as job factors, individual characteristics, and group relationships outside of work. The objective of this study is to determine the relationship between leadership style to job satisfaction among Malaysian Army College Officer. This research is based on quantitative research methodology and a cross-sectional survey research design. The 52 sample was selected by using a random sampling method to represent the whole 60 population of officer working at Army Collage in Port Dickson. Based on the findings of the study, there is no significant relationship between authoritarian leadership style and laissez-faire leadership style and there was significant relationship between democratic leadership style with job satisfaction. This means that employees were democratic leadership style with their current job, it does affected to the level of their job satisfaction and their performance. This research will give benefit to the General of Command in Training and Doctrin (GOCTRADOC) and Commandant of Center of Excellence's Malaysian Army to get competent and quality also may solve shortage qualified instructor and lecturer.